Choosing leadership a workbook - Ginzel, Linda Elaine (Ascent Audio, 2023)
Choosing Leadership gives listeners the tools to sharpen their leadership skills, putting the responsibility for personal growth and professional development in their own hands. It counters stereotypes that lead us to believe it takes a fancy title, big budget, impressive credentials, charisma, or innate leadership traits to be a "leader." Rather, leadership is a choice; you choose when to manage and when to lead. It provides an opportunity to answer tough questions of yourself, process your own life lessons, reflect on your unique experiences, and create your best future self. This process of self-discovery will help you develop individualized, customized wisdom and be your lifelong companion on the road to being wiser, younger. Now revised, with the addition of Learning Modules for each chapter, Choosing Leadership provides step-by-step guidance to create group experiences designed to enable reflection, explore ideas, and enhance self-understanding. These group experiences create collective wisdom and encourage learners to make better and more thoughtful choices. Through peer discussions, listeners learn how to coach themselves. While gaining self-understanding, they also gain confidence. They realize they know how to lead and are wiser, younger
Online resource; title from title details screen (O'Reilly, viewed March 7, 2023)
Keywords: Leadership -- Problems, exercises, etc; Success in business; Leadership; Problèmes et exercices; Succès dans les affaires; Leadership; exercise books; Audiobooks; Problems and exercises; Livres audio; Problèmes et exercices